Potential of annual forages in the Northern Great Plains. Issue 1 (4th January 2019) - Meccage, Emily; Carr, Patrick M.; Bourgault, Maryse; McVay, Kent; Boss, Darrin
Abstract : Annual forages are a good option for many farmers and ranchers in the Northern Great Plains, particularly when traditional forage sources are in short supply. Not only do they provide increased production per acre compared with perennial forages, but they also provide a quality forage source for livestock. While there are potential nutritional benefits to be gained by including non‐traditional species in the forage mix, nitrates and other potential toxins need to be considered. Earn 0.5 CEUs in Crop Management by reading this article and taking the quiz at www.certifiedcropadviser.org/education/classroom/classes/637 .